Sams teach yourself Unity 2018 game development in 24 hours - Geig, Mike (Sams, 2018)
In just 24 lessons of one hour or less, Sams Teach Yourself Unity Game Development in 24 Hours will help you master the Unity 2018 game engine at the heart of Ori and the Blind Forest, Firewatch, Monument Valley, and many other sizzling-hot games! This book's straightforward, step-by-step approach teaches you everything from the absolute basics through sophisticated game physics, animation, and mobile device deployment techniques. Every lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success. Step-by-step instructions carefully walk you through the most common Unity game development tasks. Practical, hands-on examples show you how to apply what you learn. Quizzes and exercises help you test your knowledge and stretch your skills. Notes and Tips point out shortcuts and solutions Learn how to ... Get up and running fast with the Unity 2018 game engine and editor Work efficiently with Unity's graphical asset pipeline Make the most of lights and cameras Sculpt stunning worlds with Unity's terrain and environmental tools Script tasks ranging from capturing input to building complex behaviors Quickly create repeatable, reusable game objects with prefabs Implement easy, intuitive game user interfaces Control players through built-in and custom character controllers Build realistic physical and trigger collisions Leverage the full power of Unity's Animation and new Timeline systems Integrate complex audio into your games Use mobile device accelerometers and multi-touch displays Build engaging 2D games with Unity's 2D tools and Tilemap Apply the "finishing touches" and deploy your games